The Role of Civic Education Teachers in Forming Tolerance Attitudes and Overcoming Student Conflicts at Senior High School 1 Restorasi Riung - Yuliana Mazing; Martina Rita Yuklina; Elviana Pona Rato (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
This study aims to determine the Role of Civic Education Teachers in Forming Tolerance Attitudes and Overcoming Student Conflicts at Senior High School 1 Restorasi Riung. The research method used is qualitative method. Data collection techniques in this study are using observation, interview, documentation techniques. In this study, the data source is the Civics Education teacher at Senior High School 1 Restorasi  Riung. The results obtained by researchers show that Civic Education Teachers have a strategic role in shaping students' tolerance attitudes and overcoming student conflicts through learning Pancasila values, class discussions, habituation of mutual respect for differences, and personal approaches to students who experience or trigger conflicts. In addition, in overcoming conflicts between students, the Civic Education Teacher acts as a mediator and facilitator who encourages problem solving through deliberation, open dialogue, and project-based learning activities that instill cooperation and empathy. Thus, it can be concluded that Civic Education teachers have a very important role in shaping students' tolerance and conflict resolution attitudes. This role is not only reflected in classroom learning activities, but also in social interactions in the school environment as a whole.